Unmasking factors that propel men into extramarital affairs as perceived by men in Gweru’s Mkoba suburb: Zimbabwe - Kurebwa, Mercy; Dzimiri, Wonderful (Scholars Academic and Scientific Publishers, 2016)
This paper examines the factors that propel men to engage in extramarital affairs in Mkoba suburb Gweru. Underpinned by the interpretive paradigm, data were collected through individual in-depth interviews with twenty married men and three focus groups of eight men each. Participants were purposefully selected in line with the qualitative approach employed in this study. Data were thematically analysed. It emerged from the study that indeed men engaged in extramarital affairs driven by factors that included cultural beliefs, domestic problems, men’s ego, and wife untidiness in cooking, personal hygiene and house maintenance. The study recommended counselling for married couples among other recommendations to mitigate the indulgence in extramarital affairs. Further research is recommended on a wider scale to come up with more generalisable findings and solutions.